Dual Monoclonal Antibody Therapy for a Severe Asthma Patient - Domingo, Christian; Pomares, Xavier; Morón, Anisi; Sogo, Ana (Frontiers in Pharmacology, 2020)
Introduction: Omalizumab, the first biological treatment for severe allergic bronchial asthma, has been on the market for more than a decade. Omalizumab was initially considered to be an IgE-blocking agent, and therefore, an inhibitor of the Th2 (allergic or adaptive) cascade. More recently, other monoclonal antibodies for severe eosinophilic asthma have become available, exerting an anti-eosinophilic effect basically by blocking IL5 or its receptor. These agents exert this effect regardless of the origin of the eosinophils (i.e., the adaptive or the immune system). Case study: we treated an oral corticosteroid (OC) allergic asthma patient with omalizumab. After a year of omalizumab, the improvement remained very limited and the medical team proposed discontinuation of the treatment. However, the patient considered that her asthma had improved and she refused to give up the treatment, which continued for ten years. The dose of the mean accumulated OCs was 200 mg despite what the FEV1 was low. When mepolizumab became available, since the patient had a high number of eosinophils in peripheral blood, she accepted a treatment switch to mepolizumab. One year later, clinical improvement was limited. At that time, severe symptoms of allergy reappeared. Then, a combination of monoclonal antiobodies (omalizumab and mepolizumab) was proposed. Results: after 24 months of dual therapy, a marked improvement in the FEV1 was observed which reached the normality and the OCs dose was reduced to 2.5 mg per day of prednisolone. No side effects were observed. Conclusions: in some severe allergic asthma patients with a persistently high eosinophil count in peripheral blood, when the patient is considered a non or mild responder to anti-IgE and anti-IL5 administered individually, a combination with both antibodies that covers all T2 spectrum can be effective.